Defence Diplomacy Between Indonesia And South Korea: An Indonesia Perspective - Ludiro Madu (Jurusan Ilmu Hubungan Internasional, 2015)
Defense diplomacy has significantly remarked a new phase of bilateral cooperation between Indonesia and South Korea. The improvement of Indonesia and South Korea cooperation in this new area actually reflects their shared interests towards regional dynamic in Asia. Recent development shows the presence of the US military in the region —through the US rebalance— and military modernization of China have sent mixed responses among countries in Asia. This intense condition seems to play important role as the driving force for defense diplomacy between Indonesia and South Korea. In addition, this paper also seeks to boost the necessity of both countries in enhancing the bilateral defense diplomacy in many aspects rather than just limit itself in export-import activities.